Black Truffles of Sweden : Systematics, Population Studies, Ecology and Cultivation of Tuber aestivum syn. T. uncinatum - Wedén, Christina (Uppsala universitet, Systematisk botanik, 2004)
Tuber aestivum is an ectomycorrhizal ascomycete with underground fruit bodies. It is an economically important species, but has been regarded as endangered in Sweden. My inventory has increased the number of reported localities from 3 to 31. It has long been debated whether T. aestivum and T. uncinatum are conspecific or not, so a clarification would help conservation biology and cultivation. My study included 117 fruit bodies of both taxa from 8 countries. The phylogenetic (ITS) and microscopic analyses showed that the two taxa were synonyms and that the spore reticulum height, used to separate the taxa, is not diagnostic. T. aestivum was clearly different from T. mesentericum, which I reported new to Sweden. The Gotland T. aestivum population was genetically distinct (RAPD) from other European specimens. The genetic variation suggested sexual reproduction. The habitat of 18 T. aestivum sites on Gotland were analysed and compared with data from France. No striking functional differences in soil chemistry were found, so a possible T. aestivum ecotype on Gotland would rather be an adaptation to the colder and drier climate. Selecting local T. aestivum inoculum for truffle orchards in Northern Europe could be important for successful truffle production. In 1999, 10 experimental truffle orchards with a total of 240 oak and hazel seedlings were established on Gotland, and as a result of this project 3000 commercial oak seedlings were planted in 2000-2001. In 2004, T. aestivum mycorrhiza was still present in all of the 22 orchards studied on Gotland, some in soils different from natural habitats. In addition, the project has also generated a truffle cultivation association, a truffle company, truffle dog breeding and export of T. aestivum to France.